Integrated Modelling of In-Bag Fertilizer Handling Process and Forklift Needs to Reduce Waste in Sales Warehouses of PT Petrokimia Gresik - Bachtiar Rosihan Aghda; Nurhadi Siswanto (Institut Teknologi Sepuluh Nopember, 2020)
PT. Petrokimia Gresik is one of the most outstanding fertilizer manufacturers with 5 sales warehouses. The Company organizes its distribution system to ensure adequate distribution to the right target. To plan the process of handling in-bag fertilizer, resources such as contract workers, forklifts, and trucks are needed. However, there are numerous wastes associated with the handling process, which is shown by forklift idle time due to the bagging, handling, and loading processes. Therefore, this research identifies the waste that occurs using the Value Stream Mapping (VSM) method with the 5 why’s tool. This research also uses simulation to analyze and validate the recommendations. Data obtained through questionnaires showed that waste occurs due to waiting time by 28.2% and unnecessary motion by 22.7%. The described Process Activity Mapping (PAM) tools show that fertilizer delivery has cycle times of 9030 seconds, with value-added activities of 66%. The analysis of 5 why’s tools shows that the low handling speed causes waste at the bagging and loading processes and the unnecessary motion of forklift-3. The recommendations according to the future state Value Stream Mapping (VSM) are adding the contract worker in the bagging process, removing forklift-3, and adding the contract worker in the loading process. Therefore, the value-added activity increases to 75.8% and accelerates the delivery cycle time to 7733 seconds. The validation results using the simulation shows that forklift-3 can be eliminated because it has a low utilization value of 16.4%, merging the activity of sewing services of 3% with a decrease in transfer time from 7.9 hours to 2.9 hours for one delivery cycle. In conclusion, the removal of all forklift-3 in 5 sales warehouse results shows that the company can save rental costs by Rp.4,772,376,000/year.